Why Did Ethnography Cross the Border? - Jaime Alvaro Paredes Paez (Canadian Society for Studies in Education, 2022)
Abstract:  Where is qualitative research headed? Why is ethnography so fundamental? This paper presents an examination of literature, primarily inspired by the work of Denzin and Lincoln (2018), by developing a narrative of the contemporary. The interweaving of multiple research paradigms, the advancement of the bricolage, the coalition of dynamic worldviews suggest a trans, inter, cross, multi, pluri- disciplinary landscape infused with re-imagined, re-purposed, and re-functioned ethnographic stances in social research. The present-future possibilities across the blurring borders of the contemporary become an invitation for researchers to read and narrate the human world and experiences as ever-changing, infinitely complex relational structures. Ultimately, an invitation to create transformative and humanizing utopic aesthetics.